Transcutaneous Auricular Vagus Nerve Stimulation at 20 Hz Improves Depression-Like Behaviors and Down-Regulates the Hyperactivity of HPA Axis in Chronic Unpredictable Mild Stress Model Rats - Li, Shaoyuan; Wang, Yu; Gao, Guojian; Guo, Xiao; Zhang, Yue; Zhang, Zixuan; Wang, Yifei; Zhang, Jinling; Wang, Junying; Li, Liang; Yang, Yongsheng; Rong, Peijing (Frontiers in Neuroscience, 2020)
Both animal experiments and clinical trials have confirmed that transcutaneous vagus nerve stimulation (taVNS) at auricular concha region has a curative effect on depression. However, there has been no clear evidence showing any of the stimulation frequencies is superior to the others. This study aimed to explore the different antidepressant effects of three frequencies of taVNS on chronic unpredictable mild stress (CUMS) depression model rats. In our experiment, 50 male Sprague-Dawley rats were randomly divided into five groups, i.e. the control, model, 5 Hz-taVNS, 20 Hz-taVNS and 100 Hz-taVNS group. A 30 min taVNS procedure at the above-mentioned three different frequencies and an intensity of 2 mA was administrated once a day for 28 consecutive days. The results demonstrated that rats exposed to CUMS showed various depressive-like behaviors including reduction in sucrose preference, poor performance in forced swimming test and open field test, as well as significant dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis as detected by plasma cortisol and adrenocorticotropic hormone concentration. The 28 days’ taVNS session interventions at the above mentioned three frequencies produced quite differential consequences such that, while at 20 Hz taVNS significantly reversed the depressive-like behaviors and down-regulated the hyperactivity of HPA axis, neither 5 Hz nor 100 Hz showed any anti-depressant effect on CUMS induced depressive rats. Based on these results, we propose that out of the three observed frequencies for taVNS intervention on depression, 20 Hz may be the optimized frequency to have a better modulation effect on HPA axis function by activating auricular vagus nerve.